Slang in animated cartoons: Translation peculiarities - Bondarenko, Kateryna (LingBaW. Linguistics Beyond and Within, 2019)
The research focuses on analysing the function of slang in modern cartoons (Madagascar 2, Kung Fu Panda, Shrek, Open Season, Cars) as well as translation strategies used to convey accurate meaning. Our data from film scripts (163 examples containing slang terms) has proved that slang, as an important part of cartoons’ verbal component, should be and mainly retained in translation. Excerpts from original cartoons scripts show slang use, that may function both for the protagonists’ characterisation and for the mapping of humor (carnivalesque) world picture. Componential analysis of meaning – breaking down the sense of slang terms into their minimal distinctive features – was used to determine the meaning of lexemes and reconstruct semantic domains actively verbalised by slang. The assumption has been made that due to the universality of domains slang can be potentially translated in most cases. Componential analysis is particularly applicable to semantically related lexemes (in one language or comparable ones). A thorough analysis of slang translation showed the employment of the following strategies: stylistic compensation (50.3%), literal translation (44.7%), omission (4.9%) and cultural equivalence (0.1%). As seen, a substantial proportion of the slang words can be translated from English into Ukrainian without significant loss of meaning. The neutralisation of slang appears to be inevitable in some cases.